La inteligencia emocional y el liderazgo transformacional en el patronato de Amparo Social Niño de Isinche. - Parra Muñoz, Walther Vinicio (2024)
The research entitled "Emotional Intelligence and Transformational Leadership in the Patronato de Amparo Social Niño de Isinche" In this sense, the research question seeks to identify which emotional intelligence (EI) strategies and how they contribute to strengthening transformational leadership in the Patronato Leaders. Therefore, the general objective is to develop strategies to strengthen leadership in the institution. EI is the ability to understand, perceive, and manage emotions effectively. On the other hand, the transformational leader inspires and motivates his followers to develop their maximum potential, the methodology used was quantitative, using a non-experimental and descriptive design. 50 surveys were applied to the collaborators of the Patronato, evaluating three dimensions of EI, emotional control (92%+), interpersonal intelligence (54%+), personal autonomy (78%-), and three dimensions of leadership; inspirational motivation (74%+/-), idealized behavior (78%+) and individualized consideration (96%+). The results revealed a significant positive correlation between EI and transformational leadership with a value of r = 0.560, p < 0.001, highlighting that leaders with greater EI skills demonstrate more effective and transformational leadership. Among the identified strategies are the development of self-efficacy, empathic management, and clarity in communication. In conclusion, the research highlights that EI is an important component for the development of effective transformational leadership. Finally, emphasis is placed on strategies development such as therapeutic art workshops, creativity, active listening, conflict resolution, communication skills, and self-assessment practices.